2013
DOI: 10.1002/jssc.201300418
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography/trace analysis of derivatized azelaic acid as a stability marker

Abstract: Azelaic acid, a naturally occurring saturated dicarboxylic acid, is found in many topical formulations for its various medical benefits or as a byproduct of the oxidative decomposition of unsaturated fatty acids. The poor volatility of azelaic acid hinders its applicability in GC analysis. Therefore, azelaic acid was derivatized by methylation and silylation procedures to enhance its volatility for GC analysis. Accordingly, dimethyl azelate (DMA) and di(trimethylsilyl) azelate were synthesized and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It was noted that percentage recovery was almost 100% in all situations; hence, DEA was quite resistant to chemical hydrolysis. The results are in good agreement with earlier reported results by Alzweiri et al 21 Chemical stability of aliphatic diesters was reported and studied using FT-IR and NMR by Raghunanan and Narine 35 . It was reported that when the hydrocarbon chain between the two carbonyl groups gets longer, ester bond becomes more stable 35 .…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…It was noted that percentage recovery was almost 100% in all situations; hence, DEA was quite resistant to chemical hydrolysis. The results are in good agreement with earlier reported results by Alzweiri et al 21 Chemical stability of aliphatic diesters was reported and studied using FT-IR and NMR by Raghunanan and Narine 35 . It was reported that when the hydrocarbon chain between the two carbonyl groups gets longer, ester bond becomes more stable 35 .…”
Section: Resultssupporting
confidence: 94%
“…Preparation and stability of diethyl azelate (DEA) DEA prodrug was synthesized according to the general procedure described by Alzweiri et al for the preparation of dimethyl azelate (DMA) 21 . Ethanol was used for the preparation of DEA, and an oily faint-yellow liquid was obtained.…”
Section: Methods and Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include spectrophotometric analysis employing UV/fluorescent detector or by utilizing thin layer chromatography, gas chromatography and liquid chromatography-mass spectrometry. These techniques either follow pre-column derivatization approach via 1-leucine-4-methyl-7-coumarinylamide [12] , methyl methoxy coumarin [13] , methylation/salylation [14] , 4-bromophenacylbromide/phenacetyl bromide [15,16] , 2-bromoacetyl-6-methoxynaphthalene [17] or on-column derivatization via charged dye [18] . Most of these methods are sensitive enough for the quantitative analysis of lower concentrations of AZA.…”
mentioning
confidence: 99%